2014
DOI: 10.1007/s00127-014-0985-y
|View full text |Cite
|
Sign up to set email alerts
|

Internal migration, mental health, and suicidal behaviors in young rural Chinese

Abstract: Purpose There is a dearth of data on the association of internal migration with mental health in young rural Chinese. This study aims to explore the associations between migrant status, mental health, and suicidal behaviors in young rural Chinese. Methods We recruited 1,646 rural subjects aged 16–34 years, of whom 756 were migrant workers and 890 non-migrants, from ten representative villages in rural Sichuan Province, the southwestern part of China. To assess subject's depressive symptoms and general psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
3
32
0
Order By: Relevance
“…This prevalence is higher than that found in other cohorts of Chinese general population, including urban and rural community‐residing residents (19.9% and 16%; Xiao, Ji, & Zhang, ), university students (23.8%; Lei, Xiao, Liu, & Li, ), and community older adults (23.6%; Li, Zhang, Shao, Qi, & Tian, ). Compared with the prevalence rates reported in earlier studies with samples of general migrant workers (8%‐23.7%) (Qiu et al, ; Dai et al, ; Lam & Johnston, ), this study also revealed a higher prevalence of depression in AMWs. Although it is potentially problematic to directly compare the depression prevalence of our study with that of previous studies due to various measures and definitions of depression adopted (ie, Center for Epidemiologic Studies Depression Scale vs BDI‐SF) and different methods of data collection (ie, telephone interview vs self‐administered questionnaire), this finding, nearly one third of the AMWs had clinically significant depressive symptoms, indicates that depression is very common among AMWs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This prevalence is higher than that found in other cohorts of Chinese general population, including urban and rural community‐residing residents (19.9% and 16%; Xiao, Ji, & Zhang, ), university students (23.8%; Lei, Xiao, Liu, & Li, ), and community older adults (23.6%; Li, Zhang, Shao, Qi, & Tian, ). Compared with the prevalence rates reported in earlier studies with samples of general migrant workers (8%‐23.7%) (Qiu et al, ; Dai et al, ; Lam & Johnston, ), this study also revealed a higher prevalence of depression in AMWs. Although it is potentially problematic to directly compare the depression prevalence of our study with that of previous studies due to various measures and definitions of depression adopted (ie, Center for Epidemiologic Studies Depression Scale vs BDI‐SF) and different methods of data collection (ie, telephone interview vs self‐administered questionnaire), this finding, nearly one third of the AMWs had clinically significant depressive symptoms, indicates that depression is very common among AMWs.…”
Section: Discussionsupporting
confidence: 89%
“…Coupled with the above‐mentioned psychosocial factors associated with assembly‐line work and rural‐to‐urban migration, Chinese assembly‐line migrant workers (AMWs) would be at a particular high risk of developing depression. However, to the best of our knowledge, no research has been specifically designed to address the depression issue of Chinese AMWs in spite of many studies were conducted among general migrant workers (Dai et al, ; Zhong et al, ). Furthermore, previous studies focused on the most basic socio‐demographic correlates of depression among migrant workers (Mou et al, ; Qiu et al, ; Zhong et al, ; Lam & Johnston, ; Zhong, Xu, et al, ), whereas the relationships of depression with work‐ and migration‐related factors are rarely examined.…”
Section: Introductionmentioning
confidence: 99%
“…In China, academic pressure under the examination-oriented education system, cultural differences between China and Western societies with respect to the view of social and sexual relationships, as well as limited mental health literacy and social inequity experienced by massive younger generations of internal migrants resulted in increased prevalence of anxiety, depression and other mental disorders 10–12. The examination-oriented education system of China results in a score-based friend-making criterion: adolescents prefer to make friends with those who perform better in examinations, and ignore those with poor performance.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence supporting the Healthy Migrant hypothesis demonstrated that migrants are not more vulnerable compared with nonmigrants (Dai et al, 2015;Leong, Park, & Kalibatseva, 2013;Lu & Qin, 2014;Wu & Schimmele, 2005). One study showed that individuals could choose to migrate or not according to their own will, and showed that migrant status had a positive effect on health (Lu & Qin, 2014); also, migrants demonstrated a lower risk of developing depression and suicidal thoughts within a year of their migration (Dai et al, 2015).The current study aimed to establish the relationships between social level risks (social network supports, social capital, and social cohesion) on depressive symptoms (Cheung, 2013;Jin, Wen, Fan, & Wang, 2012;Li et al, 2007;Wen et al, 2010), at least in the early phase of migration. This study, therefore, is proposed to evaluate the application of the COR theory and the Healthy Migrant hypothesis in Chinese migration.…”
mentioning
confidence: 99%
“…Evidence supporting the Healthy Migrant hypothesis demonstrated that migrants are not more vulnerable compared with nonmigrants (Dai et al, 2015;Leong, Park, & Kalibatseva, 2013;Lu & Qin, 2014;Wu & Schimmele, 2005). One study showed that individuals could choose to migrate or not according to their own will, and showed that migrant status had a positive effect on health (Lu & Qin, 2014); also, migrants demonstrated a lower risk of developing depression and suicidal thoughts within a year of their migration (Dai et al, 2015).…”
mentioning
confidence: 99%